Global void ratio of municipal solid waste for compression indices estimation - Pi, Xiaoqing (2023)
Compressibility is one of the important engineering properties of municipal solid waste (MSW) affecting the stability and functionality of a landfill. Although the correlations between MSW properties and compression parameters have been established, they either have low accuracy and small datasets or are only limited to a few specific landfills in a region. In this study, a new method using the initial global void ratio (e0*) of MSW to estimate the compression indices is developed based on a comprehensive MSW dataset. The dataset consists of 124 sets (91 laboratory and 33 field) of MSW compression results obtained from 44 studies in 13 countries with different income levels and climate conditions. We categorized MSW as a ternary mixture with biodegradable (B), reinforcing (R), and inert (I) fractions, and suggested average specific gravity values (Gs,B = 1.20, Gs,R = 1.07, and Gs,I = 2.64), respectively. The e0* values were calculated using the initial dry unit weight (γd,0) and ternary composition of MSW. The correlations between the e0* and the immediate compression index, secondary compression index induced by mechanical creep, and secondary compression index induced by bio-compression of MSW were evidently established. The results are applicable to the MSW with B = 0-79.2 %, R = 0-54.0 %, I = 2.8-100.0 %, and γd,0 = 2.0-14.2 kN/m3. A simple flowchart was established to estimate the compression indices and strains of MSW disposed on in landfills and dumpsites in countries with different income levels.